Right azygos lobe occurring with fissural and lobation anomalies (Tanzania Medical Journal, 2007)
Background: The azygos lobe is a rare anomaly of the lung that is separated from the rest of the upper lobe by an azygos fissure. The lobe is encountered mostly in the right lung but a few cases have also been described in the left lung. It occurs at a frequency of 0.25-1% and has surgical and radiological importance. For example it can give rise to opacity on the X-ray that can mimic lung pathology.Observations: The azygos lobe was observed in the upper lobe of the right lung from a 45 years old male cadaver during dissection. The apex of the lung contained a vertical fissure that isolated medially the azygos lobe. The lobe appeared columnar in shape and it measured 4.7cm long and 3.7cm wide; its posterior border contained a notch. In addition to the azygos lobe the right lung also contained an incomplete horizontal fissure and therefore was divided by an oblique fissure into two lobes. Conclusion: The current observation has documented the co-existence of an azygos lobe with incomplete horizontal fissure and two lobes on the right lung. The findings have added knowledge on the morphology of the azygos lobe and have also raised awareness that it can occur with other fissural anomalies. Keywords: Lung, Azygos lobe, Azygos fissure, Horizontal fissure Lobes, Anomalies Tanzania Medical Journal Vol. 21 (1) 2006: pp. 17-19